Calculating Charmonium Dissociation in a Coulomb Gauge QCD Quark Model - Szpigel, S.; Krein, G. [UNESP]; Marques De Carvalho, R. S. [UNESP] (AIP Publishing, 2004)
We describe the derivation of an effective Hamiltonian which involves explicit hadron degrees of freedom and consistently combines chiral symmetry and color confinement. We use a field theoretical method known as Fock-Tani (FT) representation and a microscopic relativistic quark model formulated in the context of Coulomb gauge QCD. Using this relativistic hadron Hamiltonian, we evaluate the dissociation cross section of J/ψ-ρ into D-mesons.